Morality in Public Life: The Challenge before Religion (American Journal of Islam and Society, 2002)
I am honored - and deeply humbled - to be invited by the Association of Muslim Social Scientists to deliver the Ismail al-Faruqi Memorial Lecture this evening. Professor Ismail al-Faruqi was undoubtedly one of the most accomplished and one of the most illustrious thinkers that the Muslim world has produced in recent decades. His writings, which span a whole spectrum of social concerns, have contributed immensely to a better understanding of tawhid, Islamic culture, and interfaith dialogue among both Muslims and non-Muslims. As a committed intellectual who translated ideas into action, the late Professor al-Faruqi was an honest and principled voice in the struggle for a just world. It was because of his own integrity that he regarded morality in public life as fundamental to social justice. Muslims, more than perhaps most people, should be able to appreciate the importance of morality in public life. And yet most states established in the name oflslam have failed miserably to uphold the basic standards of public morality. What explains this huge paradox? How can we bridge this yawning chasm between the ideals of which we are conscious and the realities that confront us? How will globalization help or hinder our efforts to imbue public life with moral values and principles? ...